1997
DOI: 10.1111/j.1439-0434.1997.tb00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Polysaccharide (EPS) Slime of Plant Pathogenic Bacteria in Protecting Cells to Reactive Oxygen Species

Abstract: Pseudomonas syringae pv. phaseolicola, a phytopathogenic bacterium, seemed very sensitive in planta to the adverse action of reactive oxygen species (ROS) produced by two chemical systems. The disease symptoms in host plants were also suppressed by ROS. Several other plant pathogenic bacteria (P. syringae pv. pisi, Erwinia amylovora. Xanthomonas campestris pv. pelargonii) as well as P. fluorescens were also sensitive in vitro to the inhibiting or killing action of ROS. It was shown that O2" and H2O2 were produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…Given that water availability is likely one of the most highly fluctuating factors on leaf surfaces, the heavy EPS slime within aggregates may shield the bacteria from desiccation stress by buffering the matric and osmotic potentials of their surroundings. Additionally, EPS has a role in protecting plant-associated bacteria from reactive oxygen species (59), which are often encountered on plants. It has been demonstrated that aggregated bacteria resist oxidative stress better than planktonic bacteria (101).…”
Section: Microbial Modification Of the Leaf Habitatmentioning
confidence: 99%
“…Given that water availability is likely one of the most highly fluctuating factors on leaf surfaces, the heavy EPS slime within aggregates may shield the bacteria from desiccation stress by buffering the matric and osmotic potentials of their surroundings. Additionally, EPS has a role in protecting plant-associated bacteria from reactive oxygen species (59), which are often encountered on plants. It has been demonstrated that aggregated bacteria resist oxidative stress better than planktonic bacteria (101).…”
Section: Microbial Modification Of the Leaf Habitatmentioning
confidence: 99%
“…Pseudomonas syringae cells devoid of exopolysaccharides are sensitive to ROS (12). In a study of S. meliloti, Davies and Walker (13) carried out a two-part screen for mutants sensitive to H 2 O 2 that were also defective in forming productive nitrogen-fixing nodules on alfalfa (Medicago sativa).…”
mentioning
confidence: 99%
“…In contrast, the rhizosphere, such as that of the roots of germinating seeds used in this study, is bathed in the nutrients from root exudates, and S. enterica grows exponentially on or around the roots (36). Aggregation or biofilm formation can protect bacteria from environmental stresses (37)(38)(39). Accordingly, S. enterica uses attachment factors and biofilm formation to utilize plants as vectors to mammalian hosts (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of water and nutrient availability on a leaf surface are comparable to oases in a desert (49); thus, the arrival site on the leaf predisposes a subset of bacterial cells for survival or death (50). In addition, bacterial aggregation or formation of biofilms can provide a protective layer, trap nutrients, and generally aid in stress tolerance (37)(38)(39). S. enterica biofilm mutants are significantly impaired in persistence on produce leaves (51,52).…”
Section: Figmentioning
confidence: 99%